Managing Teaching Teams effectively - Kerr, Rosie; Kulski, M. (Common Ground Publishing, 2012)
After years of reduced Government funding, high student-to-staff ratios are a now a reality in many Australian universities, alongside an increasingly casualised workforce and a growing reliance on technology enhanced teaching. At the same time, the Australian Government has set ambitious new targets in the attainment rate for bachelor degrees by 2025, which promises to lead to a further rapid expansion of the sector post 2012. In this context, the assurance of teaching quality in large enrollment courses, which are taught across multiple campuses and in various modes, poses significant challenges for course coordinators. Thus, the requirement to become an effective manager of a teaching team, which often has a high proportion of casual and contract staff, is one example of the changing nature of academic work in an increasingly complex higher education landscape. This case study explores a course coordinator’s approach to the collegial development and management of an effective teaching team in a large enrollment undergraduate Business Studies course. The aim was to improve the student learning experience and outcomes through effective teamwork and by developing a shared understanding amongst the team members of best practice in teaching and assessment.